Experimental Assessment of WLED Lamp Performance for Area Lighting Application under Mesopic Photometry System - Das, Swarnendu; Sahana, Sangita; Biswanath, Roy (International Journal of Computer Sciences and Engineering, 2025)
Human eye response is characterised by photopic spectral luminous efficiency function [V(λ)] and scotopic luminous efficiency function [V′(λ)] for photopic and scotopic vision respectively. In the mesopic zone there are no fixed response characteristics but with the increase of luminance the response shifts from scotopic to photopic region and shifts from photopic to scotopic with the decrease in luminance. Luminance level in various road lighting and area lighting installation lies in the mesopic zone. In this work experimental analysis of different lamp performances in mesopic zone for area lighting installations have been performed in both laboratory and outdoor field applications. It has been found that in both cases, changes in mesopic luminance from photopic luminance occur according to the standard CIE 191:2010. Therefore white light emitting diode (WLED) shows better photometric performance and would deliver better energy efficient performance in the mesopic zone as compared to conventional lamps i.e. high pressure sodium vapour lamp (HPSV).